Black-box attacks via the speech interface using linguistically crafted input - Bispham, MK; van Rensburg, AJ; Agrafiotis, I; Goldsmith, M (Springer, 2020)
This paper presents the results of experiments demonstrating novel black-box attacks via the speech interface. We demonstrate two types of attack that use linguistically crafted adversarial input to target vulnerabilities in the handling of speech input by a speech interface. The first attack demonstrates the use of nonsensical word sounds to gain covert access to voice-controlled systems. This attack exploits vulnerabilities at the speech recognition stage of handling of speech input. The second attack demonstrates the use of crafted utterances that are misinterpreted by a target system as a valid voice command. This attack exploits vulnerabilities at the natural language understanding stage of handling of speech input.